Analysis of risk factors for quality management to blepharoplasty based on DEMATEL‐ISM. (20th September 2022) - Zhang, Jianfei; Han, Pengpeng; Yuan, Hui; Tang, Yujun; Yang, Feng
Abstract: Objective: Blepharoplasty is a typical complex structural system, which involves many factors and the interaction among them. Therefore, it is the basis of controlling the occurrence of medical complications in blepharoplasty to clarify the hierarchical relationship of various risk factors and find out the key risk factors. Methods: On the basis of identifying the risk factors for quality management of blepharoplasty by means of literature research, questionnaire survey and expert interview, the risk factor model of blepharoplasty quality management were analyzed and constructed. The relationship between the risk factors and the degree of influence on the risk factors was studied using Decision‐Making Trialand Evaluation Laboratory and Interpretative Structural Modeling Method, and the hierarchical structure model of the risk factors for blepharoplasty quality management was obtained. Results: Six levels of risk factors in quality management of blepharoplasty were identified and classified, and the causal attributes among risk factors were determined. Six key risk factors in quality management of double eyelid surgery were determined according to centrality, and finally the above risk factors were divided into three categories: direct cause, excessive cause, and essential cause. Conclusions: This study realizes the comprehensive risk factor analysis of the complex system of quality management of blepharoplasty, which can provide reference for plastic surgeons to make safety decisions of blepharoplasty.